Evaluation of Delay Characteristics in Millimeter-Wave Wireless Communication System in High-Speed Maglev Transportation Based on Measurements in Multi-Operational States - WANG Haiming; CHEN Li; JIANG Jun (Kongzhi Yu Xinxi Jishu)
High-speed maglev transportation requires vehicle-ground wireless communication systems with real-time performance and reliability far beyond those implemented on conventional high-speed railways relying on wheel-rail contact. This paper focuses on the quantitative evaluation of delay characteristics in propulsion and operation control services implemented by millimeter-wave wireless communication systems for high-speed maglev transportation. By conducting a decoupling analysis of the transmission delay in services within high-speed maglev systems (including nodal processing and link transmission), a delay testing solution for millimeter-wave wireless communication systems is proposed as follows. The end-to-end response delay testing method is employed for bidirectional operation control services, while the timestamp recording method is adopted for unidirectional propulsion services. Field measurements and probabilistic analyses of service transmission delay were conducted using an engineering prototype on a 665-meter maglev test track in Qingdao under various operational states. Testing and analysis results demonstrated a probability exceeding 99.80% for the communication system to maintain for achieving a transmission delay of less than 50 ms in operation control services, and a probability of 100% in a transmission delay of less than 280 μs in propulsion services, representing a reduction of two orders of magnitude compared to existing LTE-M systems.